English conversation - Yates, Jean; McGraw-Hill Companies (New York McGraw-Hill Education, 2016)
Practice Makes Perfect: English Conversation gives you helpful instruction on correct pronunciation, grammar, syntax, and word usage, keeping in mind the typical problems of non-native English speakers like you. Each section includes a series of exercises that gives you extra practice in using new concepts and encourages you to construct personalized conversations
Introducing yourself and others -- Expressing opinions, likes, and dislikes -- Describing people, places, and things -- Striking up a conversation -- Making dates and appointments -- Expressing wants and needs -- Making requests and offers -- Expressing doubts and uncertainty -- Talking about future events -- Making a case or arguing a point -- Narrating a story -- Retelling a conversation -- Electronic conversation -- Appendix A: Irregular past tense and past participle forms -- Appendix B: Short tag questions and answers -- Appendix C: Glossary -- Answer key
"Comprehensive study program"--Cover
Includes index
1
Keywords: English language -- Conversation and phrase books; English language -- Textbooks for foreign speakers; English language -- Study and teaching